Impact of CEO cultural background on internal control quality: Evidence from Cameroon - Tchuiendem Nelly Joel; Arthur Benedict; Agyeiwaa Owusu Nkwantabisa (Cogent Business & Management, 2023)
This research examines the relationship which exists between the CEO's cultural background and firm's internal control quality. It further investigates whether CEO duality, board size, and CEO tenure moderate this relationship. A sample of 100 unlisted, non-financial firms in Cameroon from 2016 to 2019 was used. A panel probit model was applied to test the hypothesis. The result shows that CEOs with French cultural background have better internal control quality and fewer material weaknesses reported than CEOs with English cultural background. Moreover, the study finds that CEO duality and larger board size enhance the positive relationship which exists between the French cultural background of the CEO and the internal control quality of firms. However, the findings show no significant interaction between the CEO's tenure and internal control quality of firms.
Keywords: G34; M19; M41; M42; 650; board feature; CEO cultural background; internal control material weakness; internal control quality